Genome-wide identification and expression analysis of the polygalacturonase gene family in sweetpotato - Peiwen He; Jingzhen Zhang; Zunfu Lv; Peng Cui; Ximing Xu; Melvin Sidikie George; Guoquan Lu (BMC Plant Biology, 2023)
Abstract Background Polygalacturonase (PG), a crucial enzyme involved in pectin degradation, is associated with various plants’ developmental and physiological processes such as seed germination, fruit ripening, fruit softening and plant organ abscission. However, the members of PG gene family in sweetpotato (Ipomoea batatas) have not been extensively identified. Results In this study, there were 103 PG genes identified in sweetpotato genome, which were phylogenetically clustered into divergent six clades. The gene structure characteristics of each clade were basically conserved. Subsequently, we renamed these PGs according to their locations of the chromosomes. The investigation of collinearity between the PGs in sweetpotato and other four species, contained Arabidopsis thaliana, Solanum lycopersicum, Malus domestica and Ziziphus jujuba, revealed important clues about the potential evolution of the PG family in sweetpotato. Gene duplication analysis showed that IbPGs with collinearity relationships were all derived from segmental duplications, and these genes were under purifying selection. In addition, each promoter region of IbPG proteins contained cis-acting elements related to plant growth and development processes, environmental stress responses and hormone responses. Furthermore, the 103 IbPGs were differentially expressed in various tissues (leaf, stem, proximal end, distal end, root body, root stalk, initiative storage root and fibrous root) and under different abiotic stresses (salt, drought, cold, SA, MeJa and ABA treatment). IbPG038 and IbPG039 were down-regulated with salt, SA and MeJa treatment. According to the further investigation, we found that IbPG006, IbPG034 and IbPG099 had different patterns under the drought and salt stress in fibrous root of sweetpotato, which provided insights into functional differences among these genes. Conclusion A total of 103 IbPGs were identified and classified into six clades from sweetpotato genome. The results of RNA-Seq and qRT-PCR suggested that IbPG006, IbPG034 and IbPG099 might play a significant role in tissue specificity as well as drought and salt stress responses, which showed valuable information for further functional characterization and application of the IbPGs.